Antibacterial Fusion Proteins Enhance Moraxella catarrhalis Killing - Laabei, Maisem; Colineau, Lucie; Bettoni, Serena; Maziarz, Karolina; Ermert, David; Riesbeck, Kristian; Ram, Sanjay; Blom, Anna M. (Frontiers in Immunology, 2020)
Moraxella catarrhalis is a human-specific commensal of the respiratory tract and an opportunistic pathogen. It is one of the leading cause of otitis media in children and of acute exacerbations in patients with chronic obstructive pulmonary disease, resulting in significant morbidity and economic burden. Vaccines and new immunotherapeutic strategies to treat this emerging pathogen are needed. Complement is a key component of innate immunity that mediates the detection, response, and subsequent elimination of invading pathogens. Many pathogens including M. catarrhalis have evolved complement evasion mechanisms, which include the binding of human complement inhibitors such as C4b-binding protein (C4BP) and Factor H (FH). Inhibiting C4BP and FH acquisition by M. catarrhalis may provide a novel therapeutic avenue to treat infections. To achieve this, we created two chimeric proteins that combined the Moraxella-binding domains of C4BP and FH fused to human immunoglobulin Fcs: C4BP domains 1 and 2 and FH domains 6 and 7 fused to IgM and IgG Fc, respectively. As expected, FH6-7/IgG displaced FH from the bacterial surface while simultaneously activating complement via Fc-C1q interactions, together increasing pathogen elimination. C4BP1-2/IgM also increased serum killing of the bacteria through enhanced complement deposition, but did not displace C4BP from the surface of M. catarrhalis. These Fc fusion proteins could act as anti-infective immunotherapies. Many microbes bind the complement inhibitors C4BP and FH through the same domains as M. catarrhalis, therefore these Fc fusion proteins may be promising candidates as adjunctive therapy against many different drug-resistant pathogens.